Respuesta :
The quadratic formula is x = -b ± √b²-4ac all over 2a so insert the 1 into the a in the formula 0 into the b and -24 in to the c. so its x = 0±√0²-4(1 · -24) all over 2(1)
then solve
First, a reminder: To apply the quadratic formula, you need to write out your quadratic function in the form ax^2 + bx + c. Then a is the coefficient of the highest power of x; b is the coeff. of x, and c is the constant.
Now, apply this to the given x^2 - 24 = 0. Note that there is no x term. We must insert one: 1x^2 + 0x - 24 = 0
Comparing this to ax^2 + bx + c, we see that a=1, b=0 and c = -24.